The Well Treating Pedagogy Within the Lefebre Lever Method: The Case of the Free and Happy School - Castillo-Armijo, Pablo (Revista Saberes Educativos, 2022)
Inclusive education is a new paradigm for improving quality and equity in our educational centers, even if this means starting from scratch. This article presents some theoretical and practical problems that must be dealt with in the current Chilean educational system to advance in innovative and creative proposals that allow dreaming of an inclusive school. In particular, it is presented the Lefebre Lever Method (MLL), originated in Chile in 2012. This has had an exponential growth as an educational project of Escuela Libre y Feliz (Free and Happy School), that establishes pedagogical practices from emotionality, the well treatment of children, self-discovery and the social construction of knowledge, elements that are exportable to basic schools throughout the country to improve their academic results and the well-being of their community.